DEIXIS IN BARACK OBAMA’S EDUCATION SPEECH AT WAKEFIELD HIGH SCHOOL - Islamia, Annisa Nur; Wulandari, Tita Ratna (Jurnal Ilmiah Bina Bahasa, 2017)
Abstract: This study is aimed at analysing the five types of deixis according to Levinson (1983) that are used in Obama?s speech at Wakefield High School. It also aimed at describing the use of deixis in utterances, interpreting the references meaning, and finding out the most dominant type of deixis used. This study was conducted by using qualitative method. It was found that there are four types of deixis found such as person, temporal, spatial, and discourse deixis. The most dominant deixis found is person deixis. Person deixis consists of first, second, and third person. Person deixis was used to find out participant in the speech. Spatial deixis was used to describe a location of participant in the speech event. Temporal deixis was used to point certain period of time. Discourse deixis referred to certain discourse that contain the utterance or as a signal and its relations to surrounding text.   Keywords: Deixis, Speech, and Barack Obama.   Abstrak: Penelitian ini bertujuan untuk menganalisa lima tipe dari deiksis menurut Levinson (1983) yang dipergunakan pada pidato Obama di Sekolah Tinggi Wakefield. Penelitian ini juga bertujuan untuk mendeskripsikan penggunaan deiksis dalam percakapan, menginterpretasikan maka dari referen, dan menemukan tipe deiksis yang paling dominan. Penelitian ini menggunakan metode kualitatif. Dari hasil penelitian ditemukan bahwa ada empat tipe deiksis dalam pidato Obama, yatu orang, wake, tempat, dan wacana. Deiksis yang paling dominan muncul adalah deiksis orang, yang terdiri dari orang tunggal, kedua, dan ketiga. Deiksis orang dipergunakan untuk menemukan partisipan dalam pidato. Deiksis tempat dipergunakan untuk mendeskripsikan lokasi dari partisipan dalam pidato. Deiksis waktu dipergunakan untuk menunjukkan periode waktu tertentu. Deiksis wacana merujuk pada wacana tertentu yang mengandung ungkapan atau sebagai sinyal dan hubungannya terhadap teks yang berkaitan.   Kata kunci: Deiksis, Pidato, dan Barack Obama.